The Use of Padlet to Improve the Participation of Senior High School Students in English - Villanueva, Louie; Corpuz, Jonathan; Corpuz, Marion Shanne; Galicinao, Erica Mae; Espejo, Alfred Laurence; Empleo, Hasmin (Universitas Islam Negeri Alauddin Makassar, 2023)
This study determined the extent of participation of Grade 11 students at Mariano Marcos State University-Laboratory High School in their online English class through Padlet. Twenty-five Grade-11 students and one cooperating teacher were involved in this study. A checklist adapted from Jang (2010) was modified in order to fit to the study. In addition, observation and unstructured interview with the respondents were also conducted to validate the quantitative findings of the study. The quantitative data gathered were treated and analyzed using statistical tools such as frequency and mean while the qualitative data were analyzed and interpreted. Prior to the integration of Padlet, an observation was conducted and a pre-survey checklist was provided for the respondents to accomplish. Padlet was integrated during the demonstration teaching of the student-teacher researchers particularly during the opening motivational activity of their class. After employing Padlet in each of their three sessions, an interview was also conducted with the teacher and selected respondents to supplement the quantitative data of the study. Result showed that before integrating Padlet during online synchronous class, the mean score of the respondents is 3.23 or sometimes while after employing Padlet it was 3.63 or often. This result led to a significant impact on the extent of students’ participation and involvement in class compared to their previous performance during their online classes where PowerPoint Presentation was used as the instructional material. Thus, it is recommended for teachers to adapt and employ digital learning tools like Padlet that provide students various and creative ways to participate and be more involved during online synchronous classes.